Peran Audit Internal Dalam Meningkatkan Akuntabilitas Keuangan Pemerintah - Husain, Fauziah; Khairunnisa, Khairunnisa; Sari, Nur Indah Permata (PRODI AKUNTANSI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TJUT NYAK DHIEN (UTND), 2025)
Internal audit plays an important role in improving financial accountability and transparency in the government sector and public companies. Through its oversight function, internal audit ensures regulatory compliance and identifies potential risks in financial management. This study examines the role of internal audit in strengthening financial transparency and accountability, as well as the challenges faced in its implementation. In the era of globalization and technological development, internal audit is increasingly crucial in preventing budget abuse and maintaining the integrity of public finances. This research uses a qualitative method with a literature study approach and descriptive analysis. Data were collected from academic journals, audit reports, relevant regulations, and interviews with internal auditors and financial experts. Internal audit has proven to play an important role in ensuring regulatory compliance and reducing the risk of budget abuse. However, several key challenges remain, such as limited auditor resources, organizational resistance to transparency, and suboptimal technology adoption. Therefore, future research could focus on: (1.) Strategies to improve internal auditor competency and independence across industry sectors and (2.) Comparative studies of internal audit implementation between the public and private sectors to identify best practices in improving financial transparency and accountability.